Pendampingan Membaca Al-Qur’an dengan Metode Reward untuk Meningkatkan Maharoh Qiro’ah Santri di Musholla An-Nur Kraksaan Probolinggo - Furoidah, Asni; Ikrimah, Ilmi Mufidatul (INAIFAS Press, 2025)
It is so important to provide assistance in learning to read the Qur'an, there are still many children who have very minimal ability in terms of reading the Qur'an, in fact we often know that some of their parents are also not fluent in reading the Qur'an. There are many conditions in society where the average person has obstacles in learning the Qur'an, one of which is the ability to read. Islam educates people to always actively learn to read the Qur'an as when the first revelation came down to the Prophet Muhammad PBUH who commanded people to read the Qur'an. The purpose of this research is to increase the maharoh qiro'ah through the reward method so that the students at the An-Nur Kraksaan Probolinggo Mosque can know the basics of hijaiyyah letters in the Qur'an and feel more comfortable reading the Qur'an. In this service research, used the community service method. The results of this study state that using the reward method for students at the An-Nur Kraksaan Mosque can help make it easier for companions in the teaching and learning process. In this case, the reward method is very helpful and makes it easier for students to learn to read and recognize hijaiyyah letters.